438 Rapid Eye Movement Rebound After Continuous Positive Airway Pressure in Co-Morbid Obstructive Sleep Apnea and Fibromyalgia. (3rd May 2021) - Tapia, Gregory; Chakraborty, Sthitadhi; Padiyara, Julia; Khurshid, Abid; Rao, Murali; Meresh, Edwin
Abstract: Introduction: Fibromyalgia (FM) is a chronic pain condition that is associated with poor sleep quality and may present with obstructive sleep apnea (OSA). In OSA patients without FM, previous research has demonstrated a 57% relative increase in rapid eye movement (REM) sleep duration following treatment with continuous positive airway pressure (CPAP). However, there is limited data on REM rebound in patients with co-morbid FM and OSA. Patients with FM are often prescribed medication, like opioid analgesics, that decrease REM sleep. Additionally, pain perception may be altered by decreased REM duration. In the context of a national opioid crisis, it is imperative to explore how nonpharmacological options for treatment of co-morbid FM and OSA may improve REM sleep duration. Methods: Following IRB approval at a university-affiliated teaching hospital, an electronic medical chart review was completed on patients diagnosed with FM and OSA who received polysomnography testing (PSG) and subsequent CPAP titration treatment. REM duration and REM total sleep time (TST) percentages were reviewed at baseline PSG and after CPAP titration. Results: FM with OSA (n = 30). Mean age: 50.87, female: 28 (93%), male: 2 (7%). Baseline PSG: mean REM duration 34.47 minutes, mean REM TST 11.03%. After CPAP titration: mean REM duration 56.78 minutes, mean REM TST 18.84%. Pre- and post-CPAP titration REM TST percentage increased from 11.0% to 18.8%, indicating a mean difference of 7.8% (p < 0.001) and a 71% relative increase in REM TST percentage duration. Conclusion: These findings suggest delivery of CPAP to patients with FM and OSA improved REM sleep duration. The role of sleep in FM and pain severity is underexplored. Given the potential of chronic opioid use in patients with FM, treatment of OSA with CPAP may be a nonpharmacological alternative to pain management. Future studies are needed to see if REM rebound is associated with wellbeing, including perceived sleep quality and decreased pain perception. Support (if any):